SpiB regulates the expression of B-cell-related genes and increases the longevity of memory B cells - Horiuchi, Shu; Koike, Takuya; Takebuchi, Hirofumi; Hoshino, Katsuaki; Sasaki, Izumi; Fukuda-Ohta, Yuri; Kaisho, Tsuneyasu; Kitamura, Daisuke (Frontiers in Immunology, 2023)
Generation of memory B cells is one of the key features of adaptive immunity as they respond rapidly to re-exposure to the antigen and generate functional antibodies. Although the functions of memory B cells are becoming clearer, the regulation of memory B cell generation and maintenance is still not well understood. Here we found that transcription factor SpiB is expressed in some germinal center (GC) B cells and memory B cells and participates in the maintenance of memory B cells. Overexpression and knockdown analyses revealed that SpiB suppresses plasma cell differentiation by suppressing the expression of Blimp1 while inducing Bach2 in the in-vitro-induced germinal center B (iGB) cell culture system, and that SpiB facilitates in-vivo appearance of memory-like B cells derived from the iGB cells. Further analysis in IgG1+ cell-specific SpiB conditional knockout (cKO) mice showed that function of SpiB is critical for the generation of late memory B cells but not early memory B cells or GC B cells. Gene expression analysis suggested that SpiB-dependent suppression of plasma cell differentiation is independent of the expression of Bach2. We further revealed that SpiB upregulates anti-apoptosis and autophagy genes to control the survival of memory B cells. These findings indicate the function of SpiB in the generation of long-lasting memory B cells to maintain humoral memory.